Melanoma arising from a plaque‐type blue naevus with subcutaneous cellular nodules of the scalp. (15th October 2017) - Yan, L.; Tognetti, L.; Nami, N.; Lamberti, A.; Miracco, C.; Sun, L.; Fimiani, M.; Rubegni, P.
Summary: Plaque‐type blue naevus (PTBN) is a very rare variant of blue naevus (BN). The potential malignancy of subcutaneous cellular nodules (SCN) in PTBN was discovered in 2012, and there is currently no clear consensus on prognostic factors or management guidelines of such lesions. PTBN on the scalp have not been described in the literature. We report the clinical, histopathological and immunohistological features of a 50‐year‐old man who presented with a 30‐year history of scalp PTBN, with malignant proliferation of nodular elements and fatal outcome 8 years later. This case suggests that long‐term monitoring of patients with PTBN is required. Early surgical removal of such lesions should be considered, especially in the presence of any case of enlargement or change.